2020
DOI: 10.3390/microorganisms8030450
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transudate, a Potential Alternative to Detect Anti-Hepatitis E Virus Antibodies in Pigs and Wild Boars (Sus scrofa)

Abstract: In recent years, cases of hepatitis E virus (HEV) infection have increased in Europe in association with the consumption of contaminated food, mainly from pork products but also from wild boars. The animal’s serum is usually tested for the presence of anti-HEV antibodies and viral RNA but, in many cases such as during hunting, an adequate serum sample cannot be obtained. In the present study, liver transudate was evaluated as an alternative matrix to serum for HEV detection. A total of 125 sera and liver trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…might have a protective effect on HEV acquisition in swine (Antonio Rivero-Juarez et al, 2020 ), with a follow up study performed by the same group showing that the existence of external enteroparasites is associated with a protective effect on the likelihood of obtaining HEV, while internal enteroparasites appear to have the opposing effect by promoting HEV contamination (Rivero-Juárez et al, 2022 ). Another study evidenced that liver transudate could be used for HEV RNA detection (Navarro et al, 2020 ). A study reported HEV RNA in 27.9% (11/29) of Hyalomma lusitanicum ticks feeding on wild boars and in 34.5% (10/29) of wild boar serum samples, further typing as HEV-3 subgenotype 3f (Antonio Rivero-Juarez et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…might have a protective effect on HEV acquisition in swine (Antonio Rivero-Juarez et al, 2020 ), with a follow up study performed by the same group showing that the existence of external enteroparasites is associated with a protective effect on the likelihood of obtaining HEV, while internal enteroparasites appear to have the opposing effect by promoting HEV contamination (Rivero-Juárez et al, 2022 ). Another study evidenced that liver transudate could be used for HEV RNA detection (Navarro et al, 2020 ). A study reported HEV RNA in 27.9% (11/29) of Hyalomma lusitanicum ticks feeding on wild boars and in 34.5% (10/29) of wild boar serum samples, further typing as HEV-3 subgenotype 3f (Antonio Rivero-Juarez et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The second and last nationwide study in pig sera samples detected IgG anti-HEV in 73.3% (33/45) of animals (García et al, 2020 ). In a study that aimed to compare liver transudate with serum for the detection of antibodies in pigs and wild boars, anti-HEV was detected in 68% (85/125) of sera samples and in 61.6% (77/125) in liver transudate samples, concluding that liver transudate could be used as an alternative matrix to serum for the detection of anti-HEV antibodies (Navarro et al, 2020 ). A longitudinal long-term survey of HEV exposure in wild boar reported IgG anti-HEV in 46.7% (327/700) of animals (Barroso et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme-linked immunosorbent assay (ELISA) is a sensitive and specific analytical biochemical method that can be used for the detection and quantitative or qualitative analysis of analytes without requiring sophisticated or expensive equipment ( Ferone et al, 2020 ; Nath et al, 2020 ; Rani et al, 2021 ; Kotsiri et al, 2022 ). At present, although traditional ELISA is widely used in scientific research and testing institutions and is the ideal method for the detection of viruses and antibodies ( Leva-Bueno et al, 2020 ; Navarro et al, 2020 ; Xiao et al, 2021 ), this traditional method is time-consuming and also requires skilled operation techniques and sophisticated instruments ( Luo et al, 2020a ; Razmi et al, 2020 ; Huang et al, 2022 ). So the researchers changed the traditional approach.…”
Section: Immunological Detection Techniquesmentioning
confidence: 99%